UPAYA MENINGKATKAN KEMAMPUAN MEMBACA AL-QURAN SURAT AL-HUMAZAH DAN AT-TAKASUR MELALUI METODE REWARD AND PUNISHMENT - Ari Mawarni (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang (UIN) Raden Fatah Palembang, 2022)
This study aims to analyze the results of the application of the Reward And Punishment method in improving the ability to read al-Quran letters al-Humazah and at-Takasur in Grade VIII students of Madrasah Tsanawiyah Negeri 2 Palembang. The application of the Reward and Punishment method fulfills the diversity of learning needs in the use of children's habits and analyzes the feasibility of learning to use the Reward and Punishment method in learning to memorize verses of al-Qur'an. This study uses a quantitative method with a deductive-inductive approach through the stages of research design using two cycles, each cycle is carried out on a certain week in class VIII and the subjects are class VIII.7 MTsN 2 Palembang City as many as 23 students. Furthermore, the data that has been obtained was analyzed descriptively with the results obtained 72.39% with details of having completed learning to read the al-Quran surah al-Humazah and at-Takasur seen from the accuracy of reading pronunciation with correct recitation, aspects of memorizing with correct punctuation and fluency in reading al-Quran surah al-Humazah and at-Takasur as many as 15 children, while 8 children who have not finished. Paying attention to the results of the implementation of learning and observations achieved by the students in the first cycle, it is known that there are 8 students (34.78%) who have not completed even though the average score was obtained by the students as a whole is 72.39. Therefore, the teacher collaborates with collaborators to plan the second learning improvement activity through cycle II with the following results as many as 21 people (91.30%), while the students who have not finished are 2 people (8.70%). Thus, it is clear that there is a significant increase in the ability to read al-Quran surah al-Humazah and at-Takasur in al-Quran Hadith subjects using the Reward And Punishment method in class VIII.7 Madrasah Tsanawiyah Negeri 2 Palembang. So that it can be seen that the results of this research from before the action was taken until the first cycle and second cycle actions have been carried out there is an increase in the learning process this is because the learning method used is more interactive and more interesting so that students are more innovative and creative.